Adiponectin and leptin polymorphisms in patients with coronary artery disease - Şenol, Sefa; Tekümit, Hayrettin; Kara, Murat; Kargün, Kürşat; Yildiz, Mustafa (Baycinar Medical Publishing, 2015)
Background: In this study, adiponectin and leptin gene polymorphism were analyzed in patients with planned coronary artery bypass graft (CABG) surgeries. Methods: Between January 2012 and April 2013, 110 patients in the study group (78 males, 32 females; mean age 61.3±7.8 years; range 47 to 76 years) were scheduled for CABG surgery for coronary artery disease (CAD) and 96 healthy subjects without CAD in the control group (68 males, 28 females; mean age 59.4±8.3 years; range 46 to 78 years) were included in the study. Results: Adiponectin rs2241766 gene polymorphism and allele frequency were statistically significantly lower in the study group (p<0.05). Leptin receptor rs1137101 gene polymorphism and allele frequency were statistically significantly higher in the study group, compared to the controls (p<0.05). The rs7799039 gene polymorphism of leptin was statistically significantly higher in the control group (p<0.05), while there was no statistically significant difference in the allele frequency between the groups (p>0.05). Gene polymorphisms of adiponectin at rs1501299 and their allele frequencies were similar between the study and the control groups (p>0.05). Conclusion: Our study results showed that gene polymorphism of adiponectin at rs2241766 decreased the risk of CAD, while gene polymorphism of leptin receptor rs1137101 and rs7799039 increased the risk. By demonstrating the biochemical consequences of adiponectin and leptin polymorphisms, this study may, together with larger and more comprehensive studies, serve as a reference concerning these risks associated with these polymorphisms and the benefits of prophylaxis in CAD.
Keywords: Adiponectin; Coronary artery disease; Leptin; Polymorphism